Using Bank Savings Product Design for Empowering Women and Agricultural Development - Jose C. Galdo (Institute of Labor Economics (IZA), 2021)
This study examines whether the random allocation of single and joint saving accounts to cash crop farmers in rural Ethiopia is associated with changes in decision-making authority and control over resources that ultimately lead to changes in labor effort, schooling allocations, income, consumption, agricultural investments, and crop output. Women and children work more when joint deposit accounts are available. Likewise, meaningful effects on school participation are reported for girls. Consistent with posited channels of intrahousehold bargaining models, women from households assigned to the joint saving treatment group show significant gains in autonomy and control of savings resources, and financial empowerment. While we find substantial gains in subjective wellbeing for single and joint account experimental groups, no meaningful impacts on agricultural crop output, income, and consumption are found. However, a systematic decumulation of livestock assets is observed across households assigned to the joint account treatment group.
Keywords: C93; D14; G21; J43; I21; O12; R20; 330; bank savings; agriculture markets; labor; schooling; women empowerment; RCT